Glucocorticoid Receptor Homodimers and Glucocorticoid-Mineralocorticoid Receptor Heterodimers Form in the Cytoplasm through Alternative Dimerization Interfaces - Savory, Joanne G. A. (American Society for Microbiology, 2001)
Steroid hormone receptors act to regulate specific gene transcription primarily as steroid-specific dimers bound to palindromic DNA response elements. DNA-dependent dimerization contacts mediated between the receptor DNA binding domains stabilize DNA binding. Additionally, some steroid receptors dimerize prior to their arrival on DNA through interactions mediated through the receptor ligand binding domain. In this report, we describe the steroid-induced homomeric interaction of the rat glucocorticoid receptor (GR) in solution in vivo. Our results demonstrate that GR interacts in solution at least as a dimer, and we have delimited this interaction to a novel interface within the hinge region of GR that appears to be both necessary and sufficient for direct binding. Strikingly, we also demonstrate an interaction between GR and the mineralocorticoid receptor in solution in vivo that is dependent on the ligand binding domain of GR alone and is separable from homodimerization of the glucocorticoid receptor. These results indicate that functional interactions between the glucocorticoid and mineralocorticoid receptors in activating specific gene transcription are probably more complex than has been previously appreciated.